2022
DOI: 10.1002/slct.202201112
|View full text |Cite
|
Sign up to set email alerts
|

PIDA‐Mediated Intramolecular N‐N Bond Formation to Access 2‐Aminoindazoles and 2,2′‐Biindazoles**

Abstract: A synthesis of 2‐aminoindazole and 2,2′‐biindazole derivatives from corresponding hydrazones using phenyliodine(III) diacetate (PIDA) as oxidant is reported at ambient temperature. This oxidative intramolecular cyclization reaction proceeds through the formation of the N−N bond. This protocol is metal‐free, operationally simple, has a short reaction time, and proceeds in ethyl acetate (preferred green solvent). Indazole core moieties are well established for their biological activity similarly 2‐aminoindazoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Ynamides (241) can be easily converted into CF 3 S-substituted oxazolidine-2,4-diones (243) with a quaternary carbon centre through a PIDA-mediated trifluoromethylthiolation/ oxidative cyclization with the Shen reagent (242) and this was disclosed by He and co-workers(Scheme 84). [164] The optimized reaction parameters are: Shen'sreagent (1.5 equiv. ), PIDA (2 equiv.)…”
Section: C-hetero Bond Formationmentioning
confidence: 99%
“…Ynamides (241) can be easily converted into CF 3 S-substituted oxazolidine-2,4-diones (243) with a quaternary carbon centre through a PIDA-mediated trifluoromethylthiolation/ oxidative cyclization with the Shen reagent (242) and this was disclosed by He and co-workers(Scheme 84). [164] The optimized reaction parameters are: Shen'sreagent (1.5 equiv. ), PIDA (2 equiv.)…”
Section: C-hetero Bond Formationmentioning
confidence: 99%
“…Additionally, they are utilized as a reliable bioisosteric substitute for other heterocyclic assemblies like benzimidazole and indoles. Yadav and co-workers reported that at room temperature, 2-aminoindazole and 2,2 0 -biindazole derivatives were produced utilizing hydrazones and PIDA as an oxidant (Scheme 35) [55]. The N-N bond is formed as this oxidative intramolecular cyclization event developed.…”
Section: Construction Of Biologically Relevant Heterocycles 21 | Meta...mentioning
confidence: 99%